[Anesthesia and Alzheimer disease - Current perceptions] - Marques, AF (2018)
BACKGROUND AND OBJECTIVES: It has been speculated that the use of anesthetic agents may be a risk factor for the development of Alzheimer disease. The objective of this review is to describe and discuss pre-clinical and clinical data related to anesthesia and this disease. CONTENT: Alzheimer disease affects about 5% of the population over 65 years old, with age being the main risk factor and being associated with a high morbidity. Current evidence questions a possible association between anesthesia, surgery, and long-term cognitive effects, including Alzheimer disease. Although data from some animal studies suggest an association between anesthesia and neurotoxicity, this link remains inconclusive in humans. We performed a review of the literature in which we selected scientific articles in the PubMed database, published between 2005 and 2016 (one article from 1998 due to its historical relevance), in English, which address the possible relationship between anesthesia and Alzheimer disease. 49 articles were selected. CONCLUSION: The possible relationship between anesthetic agents, cognitive dysfunction, and Alzheimer disease remains to be clarified. Prospective cohort studies or randomized clinical trials for a better understanding of this association will be required.